The optimal transmission and dual resonant for different geometrical U-shaped THz nano antenna with surface plasmons (SPs) biosensors - Mohanad H. Aljanabi; Ahmed Hussein Duhis; Ahmed Obaid Aftan; Nadia Alanı (Institute of Advanced Engineering and Science, 2020)
In this study, we focus on plasmonic nanoantenna structures for the U shaped. We will do our simulations with FDTD method (finite difference time domain) by considering commercial software Lumerical. We use U-shaped and play with the geometrical parameters such as length (L), width (W), high (H), to enhance the transmission of light. In addition to this, we will consider the different methods and substrates. U-shaped designed structure by using gold and MgF2 materials and studied how to enhance nanoantenna coefficients to get the highest electric field improvement factor and support multi-spectral resonances, that can be tuned from visible to near-IR wavelengths. For the optimum coefficients, the proposed U-shaped nanoantenna reached the optimal transmission and multi-resonant for different geometrical size. In results shows that in this model are wideband range of wavelengths and optimal transmission and all physical boundary conditions are chosen as perfectly matched layer (PML) to avoid undesired reflections, when we change the size of U-shaped with different materials is used and gets more proposes in the biosensors, biomedical and laser optical communication and for nanoantennas can also be deposited on layered substrates to enable solar cells and energy harvesting applications .And we can see that there are two resonances at (????1 and ????2) wavelength range (500-950) nm, the first one has a transmission 0.73 at wavelength 700nm; and the other one has a transmission 0.88 at wavelength 845nm from this designed. We will investigate the structure of nanoantenna to be used as biosensors.